Asuhan Keperawatan Pada Ny. T Keluarga Tn. D Dengan Gangguan Sistem Kardiovaskuler: Hipertensi Di Desa Tonjong Dukuh Kauman RT 03 RW 04 Kecamatan Tonjong Kabupaten Brebes - Merimbi Gita Yunia; Siti Fatimah (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
Introduction: Hypertension is an increase in systolic blood pressure ≥140 mmHg and/or diastolic ≥90 mmHg that has the potential to cause serious complications. The prevalence of hypertension in Indonesia is 34.11% (Riskesdas, 2018), in Central Java 37.57%, and in Tonjong Village 15,951 patients aged ≥15 years were recorded (Tonjong Health Center, 2025). Purpose: To provide direct and comprehensive family nursing care to Ny. T, the family of Tn. D, with hypertension in Tonjong Village, Dukuh Kauman RT 03 RW 04, Tonjong District, Brebes Regency. Method: Case study with a nursing process approach. Data were collected through interviews, observation, physical examination, and documentation, conducted on December 26–29, 2025. Results: Assessment revealed that Ny. T complained of dizziness, neck pain, difficulty sleeping, and soreness in both legs with blood pressure of 167/100 mmHg. The family had no knowledge about hypertension. Two diagnoses were established: Acute Pain (D.0077) and Knowledge Deficit (D.0111). Interventions included complementary foot massage therapy to address acute pain and health education on hypertension. After three visits, the Acute Pain diagnosis was partially resolved with a decrease in pain scale from 3 to 2 and blood pressure from 167/100 mmHg to 150/95 mmHg, while the Knowledge Deficit diagnosis was fully resolved. Conclusion: Family Nursing Care with the SDKI, SLKI, and SIKI approach had a positive impact on improving the condition of Ny. T. It is recommended that the client continue foot massage independently, implement the five family health tasks, and routinely utilize health facilities.